2017
DOI: 10.1590/2317-1545v39n3180280
|View full text |Cite
|
Sign up to set email alerts
|

Luminosity and sowing depth in the emergence and development of passion fruit seedlings

Abstract: -The propagation of passion fruit in commercial orchards is carried out by seeds. However, passion fruit seed germination occurs irregularly. The goal of this study was to evaluate the emergence and development of passion fruit seedlings under different luminosities and sowing depths. The experimental design was completely randomized with six replications of 25 seeds, with a 3 x 5 factor scheme, in which three light conditions (absence of light, presence of 12 h light and 12 h dark and the presence of light fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…seeds do not depend on light and dark conditions for germination percentage. And the result is also reinforced by the study by Ribeiro et al (2017), who evaluated three periods of light exposure (0, 12, and 24 h) in P. edulis seeds set to germinate at an alternating temperature of 20/30 ºC, obtained a significant difference in germination between the tested periods of light exposure. The average percentage of emergence was 83, 92, and 86 %, respectively.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…seeds do not depend on light and dark conditions for germination percentage. And the result is also reinforced by the study by Ribeiro et al (2017), who evaluated three periods of light exposure (0, 12, and 24 h) in P. edulis seeds set to germinate at an alternating temperature of 20/30 ºC, obtained a significant difference in germination between the tested periods of light exposure. The average percentage of emergence was 83, 92, and 86 %, respectively.…”
Section: Resultsmentioning
confidence: 69%
“…Maciel e Bautista (1997) obtained a higher percentage of germination in dark conditions, with reduced values during exposure to light, and concluded that passion fruit seeds are negatively photoblastic. Ribeiro et al (2017) found that passion fruit seeds exposed to dark periods had higher emergence values compared to those exposed to continuous light or continuous dark, inferring that passion fruit seeds need periods in the absence of light to trigger the process of germination.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, the success of seed utilization depends on a rapid and uniform emergence of seedlings in the nursery or field (Barros et al, 2010;Vieira et al, 2015). The delay in emergence of seedlings leaving the seeds more vulnerable to attack from predators (pests and pathogens) and unfavorable environmental conditions (temperature, substrate moisture, among others) and, therefore, compromise the establishment of a uniform stand (Silva et al, 2017b;Ribeiro et al, 2017). The cultivation of a native species depends on the technical knowledge, spread and growing environment of this species.…”
Section: Introductionmentioning
confidence: 99%